2012
DOI: 10.1177/1933719111413300
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Levels of Serum Pigment Epithelium-Derived Factor in Women With Endometriosis

Abstract: The authors previously demonstrated decreased levels of pigment epithelium-derived factor (PEDF) in peritoneal fluid of women with endometriosis compared to women without endometriosis. Here, the authors determine whether women with endometriosis have altered levels of PEDF in serum. Peripheral blood samples were collected from 71 women with and without endometriosis (n = 43 and 28, respectively) before laparoscopic surgery. Concentrations of serum PEDF were measured by enzyme-linked immunosorbent assay. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Pigment epithelium-derived factor (PEDF) is an inhibitor of angiogenesis with neurotrophic and anti-inflammatory properties, and modified values of this molecule have been found in endometriotic patients. Chen et al [104] analyzed the serum levels of PEDF in 43 women with laparoscopically confirmed endometriosis and 28 controls, using the enzyme-linked immunosorbent assay. The results of their study indicated that PEDF was significantly decreased (16.3 ± 6.6 ng/mL) in cases compared to controls (24.5 ± 7.3 ng/mL) and was correlated with the severity of the symptoms.…”
Section: Angiogenesis Moleculesmentioning
confidence: 99%
“…Pigment epithelium-derived factor (PEDF) is an inhibitor of angiogenesis with neurotrophic and anti-inflammatory properties, and modified values of this molecule have been found in endometriotic patients. Chen et al [104] analyzed the serum levels of PEDF in 43 women with laparoscopically confirmed endometriosis and 28 controls, using the enzyme-linked immunosorbent assay. The results of their study indicated that PEDF was significantly decreased (16.3 ± 6.6 ng/mL) in cases compared to controls (24.5 ± 7.3 ng/mL) and was correlated with the severity of the symptoms.…”
Section: Angiogenesis Moleculesmentioning
confidence: 99%
“…Tshoneret et al (2011) demonstrated that the reduction in the concentration of PEDF could be associated with weight and fat loss (low BMI) and the concentration of insulin and triglycerides. It is worth noting that Chen et al (2012) found no differences in the concentration of PEDF in the serum of women at different phases of the sexual cycle. These observations are consistent with the results of our study, as we have not found statistically significant variations in the expression of this protein in the first 2 months of lactation.…”
Section: Discussionmentioning
confidence: 76%
“…This further supports a fact that PEDF inhibits the growth of endometriotic cells not only by anti-neovascularization but also through the apoptosis of endometriotic cells themselves. Nevertheless, VEGF expression was decreased in vitro and vivo when PEDF treatment, suggesting an important role of VEGF playing in the pathogenesis of endometriosis [29], [30], [39], [40]. Apparently, the adjustment of an imbalance of VEGF and PEDF may be an important mechanism of PEDF gene therapy for endometriosis.…”
Section: Discussionmentioning
confidence: 98%
“…As a natural inhibitor of angiogenesis, PEDF may be more active against endometriotic lesions at the formation stage [26], [30]. Actually, many anti-angiogenic factors including COX-2 inhibitors used to treat endometriosis in animal models exert their effects at this stage [6], [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation